Bridging the gap in neonatal resuscitation in Zambia - Mutesu-Kapembwa, Kunda; Lakhwani, Jyoti; Benkele, Rodgers Gift; Machona, Sylvia; Shamalavu, Mwila Sekeseke; Chintende, Jean Musonda; Chisela, Susan Mwila; Kapoma, Sharon; Mwanza, Jackson; Chelu, Wisdom; Mwendafilumba, Martha; Kapembwa, Kenneth; et al. (Frontiers in Pediatrics, 2022)
Neonatal resuscitation has been poorly instituted in many parts of Africa and most neonatal resuscitation algorithms are adapted from environments with abundant resources. Helping Babies Breathe (HBB) is an algorithm designed for resource-limited situations and most other algorithms are designed for resource-rich countries. However, there are neonatal referral centers in resource-limited countries who may provide more advanced resuscitation. Thus, we developed a neonatal resuscitation algorithm for a resource-limited country (Zambia) which considers more advanced interventions in situations where they can be provided. The algorithm described in this paper is based on the Newborn Life Support algorithm from the UK as well as the HBB algorithm and accounts for all situations in a resource-limited country. Most importantly, it focuses on non-invasive ventilation but includes advice on more advanced resuscitation including intravenous access, fluid management, chest compressions and adrenaline for resuscitation. Although intubation skills are included in neonatal training workshops, it is not the main focus of the algorithm as respiratory support equipment is scarce or lacking in most health facilities in Zambia. A home-grown neonatal resuscitation algorithm for a resource-limited country such as Zambia is likely to bridge the gap between limited situations requiring only bag and mask ventilation and better equipped institutions where more advanced resuscitation is possible. This algorithm will be rolled out in all training institutions and delivery facilities across Zambia over the next months.